Closing or Reproducing the Gender Gap? Parental Transmission, Social Norms and Education Choice - Maria Knoth Humlum; Anne Brink Nandrup; Nina Smith (Institute of Labor Economics (IZA), 2017)
Over the last decade, the economic literature has increasingly focused on the importance of gender identity and sticky gender norms in an attempt to explain the persistence of the gender gaps. Using detailed register data on the latest cohorts of Danish labour market entrants, this paper examines the intergenerational correlation in gender-stereotypical choice of education. Although to some extent picking up inherited and acquired skills, our results suggest that if parents exhibit gender stereotypical labour market behaviour, children of the same sex are more likely to choose a gender stereotypical education. The associations are strongest for sons. Exploiting the detailed nature of our data, we use birth order and sibling sex composition to shed light on the potential channels through which gender differences in educational preferences are transmitted across generations. We propose that such transmissions may attenuate the final closing of the gender gap.
Keywords: I23; J16; J24; 330; intergenerational transmission; gender differences; gender identity; social norms